ANALISIS PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM UPPKS DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN KEBONSARI KABUPATEN MADIUN - Durrotu’aini Perwitasari Sutoyo (Universitas Darul Ulum, 2020)
Regional development is development carried out at levels and changes over a certain period of time with a set of variables and returns for factors (factor returns) in an area in one way, namely poverty alleviation, one of which is through COMDEV. The purpose of this study was to analyze the effect of regional development on poverty alleviation efforts and local government efforts in poverty alleviation through the UPPKS Comdev program in Kebonsari District, Madiun Regency. With a qualitative descriptive research approach, the type of case study is in Kebonsari District, Madiun Regency with 13 villages using the Stratified Random Sampling technique, obtained samples from pre-prosperous and prosperous families I each village as many as 8 people, so the total sample size is 104 people. Data collection techniques using field studies and literature studies. It was found that there was a significant influence on regional development on poverty alleviation efforts in Kebonsari District, Madiun Regency. And there is no significant influence of the UPPKS Comdev program on poverty alleviation in Kebonsari District, Madiun Regency. The lack of influence of the UPPKS Comdev program in Kebonsari District, Madiun Regency is caused by the lack of aspects of increasing insight and knowledge; aspects of implementing leadership styles as well as aspects of providing capital assistance and the lack of ATTG (Appropriate Technology Tools) assistance received.